(untitled) (Bioagro, 2022)
Tarragon (Artemisia dracunculus L.) is an aromatic and medicinal plant, with great export potential and competitive commercial value, so it is essential to evaluate strategies aimed at increasing the production of the crop. The objective of the present study was to evaluate the growth of tarragon cultivated in greenhouse in response to the inoculation of Trichoderma harzianum (Rifai) and Glomus cubense (Y. Rodr. & Dalpé), and the combination of both. The study was conducted in Cuernavaca, Morelos, Mexico, where tarragon seedlings inoculated with T. harzianum and G. cubense were used. The crop growth was assessed at transplantation, and at 60 days after transplantation; in each sampling leaf area, greenness index (SPAD units), weight of dry biomass in each plant were measured. The relative growth rate and absolute growth rate of the crop were also calculated. The largest leaf area, greenness index, dry biomass, relative growth rate and absolute growth rate of the crop, were obtained with the co-inoculation of T. harzianum and G. cubense. The individual application of T. harzianum generated a better response in the variables evaluated compared to G. cubense. In conclusion, inoculation of rhizospheric microorganisms increased the growth in the tarragon crop.